FORMULASI KEBIJAKAN AKUNTANSI PEMERINTAH DAERAH - Herman CMS Rumlus (DINAMIS, 2017)
This research is conducted to comprehend the Formulation Process of Merauke Regency Accounting Policy and to find out the proponent and obstruction factors due to the process of formulation.The approach of this research is analytical qualitative. Informants taken of this research are Head of Finance and Regency Asset Managerial Bureau in Merauke Regency, Head of Accounting Division and Head of Treasury Division, Head of Documentation Section of Regency Secretariat Law Division in Merauke Regency, also experts used in the process of policy arrangement. Data collected by using interview method which is then processed with “snowball” technique.From the result of this research will be then comprehended how the policy arrangement process are conducted, started from policy issues to the decision or ratification of the policy. It can be seen from the result that policy issues are being responded by the release of Ordinance about Government Accounting Standard Based on Accruals which then being followed by Minister of Home Affairs’ Ordinance for Implementation of Accruals Accounting Application. Initial phase is by making team of Policy Arrangement in Regency Government which then followed by a discussion of the team and experts, and also related officers in local government. The most affecting factors are dominated by old behavior related to the application of the policy implementation.Regent ordinance about Merauke Regency Accounting Policy is the instruction of Government Rules which later be arranged in Minister of Home Affairs’ rule about the Implementation of Accounting Standard in Regency Government, the arrangement team involves experts or academician as masters of policies who has been chosen by Head of Finance and Assets Executives, public process has involved related division and treasurer as impacted party of this policy. By doing discussion and socialiszation, this policy arrangement – which is done by policy experts and related division – has applied easier alternatives under the obedience of the regulation.There is no obstruction factor in this arrangement process then by far it can be called a success since the team, experts, and institutions has done a good communication and coordination during the process. But still the old behavior holds the most dominant effect in this formulation.Efforts done in this phase of policy arrangement – from team assembling of demand issues to discussed material through the forum – involved stakeholders which then be settled as occured procedure.